Communication between nursing staff and clients unable to communicate verbally (Revista Latino-Americana de Enfermagem, 2007)
This is an experience developed during the Master program in Nursing at UFSC. It aimed to reflect on the nursing care delivered to the patient unable to verbally communicate, based on Paterson and Zderad's Theory and to analyze the communicational process between nursing and client. The experience was carried out in the Intensive Care Center of a private hospital in two stages: non-participating observation and three existential workshops, involving nine nursing technicians. Each participant acquired self knowledge and was known by other participants in the intuitive dialogue. Alternatives of non-verbal dialogue were suggested during the scientific dialogue. The scientific-intuitive fusion emerged when there was a need of each one to position themselves about the totality. The study on the communicational process revealed the need to enlarge the approach regarding the care to the client unable to verbally communicate, especially training the team for the interpersonal and dialogical relationship.